Internet-Delivered Exposure-Based Cognitive-Behavioral Therapy for Adolescents With Functional Abdominal Pain or Functional Dyspepsia: A Feasibility Study. Issue 1 (January 2019) - Bonnert, Marianne; Olén, Ola; Lalouni, Maria; Hedman-Lagerlöf, Erik; Särnholm, Josefin; Serlachius, Eva; Ljótsson, Brjánn
Abstract: Functional abdominal pain (FAP) and functional dyspepsia (FD) are common in adolescents and associated with low quality of life. Exposure-based cognitive-behavioral therapy (CBT) is efficient for adult and adolescent irritable bowel syndrome (IBS), but has never been evaluated for adolescent FAP/FD. The aim of this study was to evaluate the feasibility and potential efficacy of a novel disorder-specific Internet-delivered CBT (Internet-CBT) for adolescents with FAP or FD, using an uncontrolled open pilot including 31 adolescents. The Internet-CBT consisted of 10 weekly online modules, which focused mainly on exposure to abdominal symptoms. Parents received modules to help them reduce unhelpful parental behaviors. Participants reported the treatment to be credible, and an overall satisfaction with the treatment. Data attrition rate was low (7%) and adherence to treatment was acceptable. We saw a significant and large effect on the primary outcome, pain intensity, at posttreatment ( d = 1.20, p < .001) that was further improved after 6 months ( d = 1.69, p < .001). Participants also made significant and large improvements on gastrointestinal symptoms ( d = 0.84, p < .001) and quality of life ( d = 0.84, p < .001) that were sustained or further improved at follow-up 6 months after treatment. This study demonstrated that exposure-based Internet-CBT, tailored for adolescents with FAP or FD, is a feasible treatment that potentially improves pain intensity, gastrointestinal symptoms, and quality of life. Highlights: Internet-CBT for adolescent FAP and FD is a feasible treatment. Internet-CBT may substantially improve symptom severity and quality of life. An adapted exposure-based protocol for FAP/FD may be a viable treatment.